2014
DOI: 10.1530/jme-14-0134
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs and the control of hormonal signaling via nuclear receptor regulation

Abstract: Despite its identification over 100 years ago, new discoveries continue to add to the complexity of the regulation of the endocrine system. Today the nuclear receptors (NRs) that play such a pivotal role in the extensive communication networks of hormones and gene expression remain an area of intense research. By orchestrating core processes, from metabolism to organismal development, the gene expression programs they control are dependent on their cellular context, their own levels, and those of numerous co-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 103 publications
(104 reference statements)
0
4
0
1
Order By: Relevance
“…On the other hand, Drosha is responsible for the cleavage of pri-miRNAs into pre-miRNAs, and then further processed by Dicer to produce mature miR-33a (Krol et al, 2010 ). Direct interaction of PPAR-γ with Drosha may thus decrease mature miR-33a biogenesis (Ottaviani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Drosha is responsible for the cleavage of pri-miRNAs into pre-miRNAs, and then further processed by Dicer to produce mature miR-33a (Krol et al, 2010 ). Direct interaction of PPAR-γ with Drosha may thus decrease mature miR-33a biogenesis (Ottaviani et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hormone receptors could be interconnected with lncRNAs expression in the cells and this relation could affect cellular metabolism (37). Moreover, in SNHG6 203 overexpression situation, the complicated behavior of MCF7 and SK-BR3 cells could be attributed to different hormonal signaling (38,39). Overall, the results of this study demonstrated an interconnection between SNHG6 203 RNA and HER2 status of breast tumoral cells that might indicate SNHG6 203 probable role in the cell cycle progression of HER2-negative breast cancers.…”
Section: Discussionmentioning
confidence: 66%
“…Recently RARα was identified to regulate protein synthesis to some extent by its binding to a subset of mRNAs in human platelets 43 . Hence, it is possible that other NRs including PXR (in a bound or unbound state with RXR) may also contribute to some level of protein translation even in the absence of a nucleus 44,45 . To date, we have found no evidence to indicate the formation of NR homodimers in platelets.…”
Section: Discussionmentioning
confidence: 99%